Kompetensi Guru PAI Alumni Jurusan Pendidikan Agama Islam Fakultas Tarbiyah dan Ilmu Keguruan IAIN Lhokseumawe di Sekolah dan Madrasah di Kabupaten Aceh Utara - Syahrizal, Syahrizal; Hasan, Fauzan; Aula, Darul; Damayanti, Damayanti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
This study is aimed at acknowledging the percentage of pedagogical, personality, social, and professional competencies of Islamic Education teachers as alumni at the Islamic Education Department of Tarbiyah in schools and Madrasahs throughout North Aceh District. This research on tracer study is a quantitative descriptive study through a survey approach. Respondents were alumni of the Islamic Education Department of Tarbiyah graduating in 2006-2010 who worked as teachers in schools and Madrasahs in North Aceh District, with a sample of 25 PAI teachers; taken by purposive sampling. Data were analyzed by inputting data from questionnaires, then analyzed statistically, presented in graphical form, and finally concluded. The results showed that the pedagogical competence of Islamic Education graduates was categorized well with a percentage of 79.67%. Teacher's personality competence is a very good category by obtaining the highest percentage of 84.50%. Teacher's social competency reaches 81.74%, this percentage is also a very good category. Teacher professional competence has a percentage of 80.67%, indicating a very good category.